An adaptive, negative feedback circuit in a biohybrid device reprograms dynamic networks of systemic inflammation in vivo - Namas, Rami A.; Mikheev, Maxim; Yin, Jinling; Barclay, Derek; Jefferson, Bahiyyah; Mi, Qi; Billiar, Timothy R.; Zamora, Ruben; Gerlach, Jorg; Vodovotz, Yoram (Frontiers in Systems Biology, 2023)
Systemic acute inflammation accompanies and underlies the pathobiology of sepsis but is also central to tissue healing. We demonstrated previously the in vivo feasibility of modulating the key inflammatory mediator tumor necrosis factor-alpha (TNF-α) through the constitutive production and systemic administration of soluble TNF-α receptor (sTNFR) via a biohybrid device. We have now created multiple, stably transfected human HepG2 cell line variants expressing the mouse NF-κB/sTNFR. In vitro, these cell lines vary with regard to baseline production of sTNFR, but all have 3.5-fold elevations of sTNFR in response to TNF-α. Both constitutive and TNF-α-inducible sTNFR constructs, seeded into multi-compartment, capillary-membrane liver bioreactors could reprogram dynamic networks of systemic inflammation and modulate key physiological outcomes in both endotoxemic and septic rats. Thus, control of TNF-α may drive a new generation of tunable biohybrid devices for the rational reprogramming of acute inflammation.